Institutions, Voids, and Dependencies: Tracing the Designs and Robustness of Urban Water Systems - Aaron Deslatte; Elizabeth A. Koebele; Lauren Bartels; Adam Wiechman; Sara Alonso Vicario; Celeste Coughlin; Desi Rybolt (International Review of Public Policy)
Urban water systems across the United States are facing a variety of challenges to existing supply and demand dynamics. Responding to these challenges in complex socio-environmental systems (SES) requires integrating various types of information – ranging from hydrologic data to political considerations and beyond – into policy and management decisions. However, the design of institutions, i.e., the formal rules in which urban water utilities are embedded, impact the flow of information, especially across diverse actor groups critical to developing and implementing policy or programmatic responses to signal error. This study develops a Bayesian application of the Robustness of Coupled Infrastructure Systems (CIS) Framework to analyze how the institutional design of a major U.S. urban water system impacts information flow and, ultimately, the goal of resource-delivery robustness. We utilize process-tracing along with an institutional analysis approach called the Institutional Grammar Tool (IGT) to parse formal institutions into their semantic and syntactic components and assess how they may influence a system’s capacity to respond to changing stressors. Our findings have important implications for the (re)design of institutions that better facilitate information flow among key policy actors and support policy changes that promote sustainable long-term urban water supply.